Are Demographic Attributes and Firm Characteristics Drivers of Gender Diversity? Investigating Women’s Positions on French Boards of Directors - Nekhili, Mehdi; Gatfaoui, Hayette (2013)
In this article, we examine the factors determining the representation of women on boards of directors by considering three main questions. The first question deals with the relationship between characteristics of ownership and governance on one side, and female directorship on the other. The second major question concerns the demographic attributes of women directors, such as nationality, foreign experience, educational level, business expertise, and connections to external sources. The third important question refers to women in senior positions on French boards (e.g., as independent members or board subcommittee members) in relation to firm characteristics and women’s demographic attributes. Our study focuses on French large- and mid-capitalized companies belonging to the SBF120 stock market index during a 5-year period running from 2000 to 2004. First, our results give evidence that the appointment of women directors is strongly related to family ownership and board or firm size. Second, the appointment of women directors is related to their professional services, valuable skills, and network links. Furthermore, we show that women face a double glass-ceiling problem, and note that French firms rely more on the demographic attributes of their women directors when they are appointed to senior board positions. Our study sheds light on issues concerning the law that comes into force in 2016, which imposes quotas of women members on boards of directors in French companies.
Keywords: Ownership structure; Gender diversity; Ethics; Demographic attributes; Corporate Governance; Board of directors